Telangana Leave Rules bare act/rules (for departmental test) - Reddi, Padala Rama (Hyderabad Panchayat Publication, 2023)
This book comprises the Leave Rules, 1933 of Telangana State.
Keywords: Public Administration; Leave Rules; Leave rules-Telangana